How hard should we push the poor to save for retirement? - Andrew G. Biggs (American Enterprise Institute (AEI), 2017)
More than half of U.S. states are working to establish programs what would automatically enrollment in Individual Retirement Accounts (IRAs) workers who are not offered a retirement plan by their employer. But the designers of state-run auto-IRA plans fail to consider three questions: Do the poor need to save more for retirement? Will state-run auto-IRA plans increase net household savings? And, after accounting for interactions with means-tested government transfer programs, will state-run auto-IRA plans make the poor better off? The answer to all three questions may be – no.
Keywords: A; 330; Retirement; savings; IRA